2009
DOI: 10.1094/php-2009-0513-01-rv
|View full text |Cite
|
Sign up to set email alerts
|

A Standard Greenhouse Method for Assessing Soybean Cyst Nematode Resistance in Soybean: SCE08 (Standardized Cyst Evaluation 2008)

Abstract: The tactic of choice for managing soybean cyst nematode (SCN) in infested fields is the use of resistant cultivars. Because expression of SCN resistance is dependent on the occurrence and frequencies of genes for virulence in SCN populations, labeling of SCN-resistant cultivars can be difficult and, occasionally, highly misleading, leading to unanticipated yield losses. The authors' objective was to offer a set of standards for assessing and labeling SCN-resistant cultivars that would allow farmers to make dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 18 publications
(15 reference statements)
0
43
0
Order By: Relevance
“…Luzzi et al (1987) screened 2370 lines of the Southern Germplasm Collection (MG V-VIII) and identified 61 lines carrying resistance to SRKN. established method (Arelli et al, 2000;Brown et al, 2010) in accordance with the Standardized Cyst Evaluation 2008 Protocol (Niblack et al, 2009) between 2008 and 2016. Hussey et al (1991) evaluated 139 southern soybean cultivars (MG V-VIII) and reported 28 with high and moderate resistance to SRKN.…”
Section: Evaluation Of Soybean Germplasm For Resistance To Multiple Nmentioning
confidence: 99%
“…Luzzi et al (1987) screened 2370 lines of the Southern Germplasm Collection (MG V-VIII) and identified 61 lines carrying resistance to SRKN. established method (Arelli et al, 2000;Brown et al, 2010) in accordance with the Standardized Cyst Evaluation 2008 Protocol (Niblack et al, 2009) between 2008 and 2016. Hussey et al (1991) evaluated 139 southern soybean cultivars (MG V-VIII) and reported 28 with high and moderate resistance to SRKN.…”
Section: Evaluation Of Soybean Germplasm For Resistance To Multiple Nmentioning
confidence: 99%
“…The FI is calculated as FI = (Nx/Ns) × 100, where Nx is the average number of females on the test cultivar and Ns is the average number of females on the standard susceptible cultivar (Golden et al 1970;Riggs & Schmitt 1988Niblack et al 2002;Klink et al 2009a, b;Matthews et al 2013). Various levels of resistance have been designated, based on the calculated FI (Niblack et al 2009). These levels include 0-9, highly resistant; 10-24, resistant; 25-39, moderately resistant; 40-60, low resistant; >60, not effectively resistant.…”
Section: Fi Analysismentioning
confidence: 99%
“…SCN race 3 (H. glycines-type 0) was maintained in greenhouse culture on cv Williams 82 using standard procedures (Niblack et al, 2009). …”
Section: Plant and Nematode Materialsmentioning
confidence: 99%